NG2 cells (polydendrocytes) in brain physiology and repair - Nishiyama, Akiko; Suzuki, Ryusuke; Zhu, Xiaoqin (Frontiers in Neuroscience, 2014)
NG2 cells, also referred to as oligodendrocyte precursor cells or polydendrocytes, represent a major resident glial cell population that is distinct from mature astrocytes, oligodendrocytes, microglia, and neural stem cells and exist throughout the gray and white matter of the developing and mature central nervous system (CNS). While their most established fate is the oligodendrocyte, they retain lineage plasticity in an age- and region-specific manner. During development, they contribute to 40% of protoplasmic astrocytes in the ventral forebrain. Despite intense investigation on the neuronal fate of NG2 cells, there is no definitive evidence that they contribute substantially to the neuronal population. NG2 cells have attributes that suggest that they have functions other than to generate oligodendrocytes, but their exact role in the neural network remains unknown. Under pathological states, NG2 cells not only contribute to myelin repair, but they become activated in response to a wide variety of insults and could play a primary role in pathogenesis.